ANALISIS KARAKTERISTIK PARKIR KARYAWAN DAN BUKAN KARYAWAN (STUDI KASUS JALAN BANDA ACEH – MEDAN KM 9 – KM 9,5 DESA LAMBARO KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR) - Rachmad Muchlas; Renni Anggraini; Irin Caisarina (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Employees who work in the Jantho city parked vehicle in the Lambaro village Ingin Jaya subdistrict Aceh Besar district. Lack of parking locations motorcycle and car causing the vehicle to be chaotic parking. This study aims to analyze the characteristics of the street parking in Banda Aceh – Medan road KM 9 - KM 9,5 . Primary data is data volume required duration of parking and parking, then the data were analyzed using analysis of the characteristics of the park include the calculation of the volume of parking, the average duration of parking, parking capacity, indexes parking and parking plot needs. Results of the analysis showed that the characteristics of parking street parking conditions Banda Aceh - Medan road KM 9 - KM 9,5 already can not accommodate parking requests motorcycle and car. Number of parking plots needs at that location is for motorcycle are as much as 275 stall and parking for car are 44 parking stalls.